(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The concept is the object of study of both cognitive linguistics and linguoculturology. The concept is a mental structure that is a basic unit of the human thinking code that has a relatively ordered internal structure, a complex, encoded information about the subject or event that is reflected and expressed as a result of cognitive activity.